1263 The Effect of Sex on Outcome of Preterm Infants - A Population-Based Survey. (October 2012) - Neubauer, V; Griesmaier, E; Ralser, E; Kiechl-Kohlendorfer, U
Abstract : Background and Aim: Forty years ago the so-called "male disadvantage hypothesis" as an explanation for increased perinatal morbidity in boys as compared to girls was introduced by Naeye et al. Since then numerous studies have confirmed the risk of being born a boy, especially when born preterm. The aim of the current study was to show comprehensive data on potential sex differences in maternal and neonatal characteristics, short-term morbidity and neurodevelopmental outcome within an entire geographically-determined collective of infants born at a gestational age <32 weeks. Methods: Between 2003 and 2008 we prospectively enrolled all infants born in Tyrol at < 32 weeks of gestation; the association between sex and a wide set of pre- and postnatal factors, post-discharge morbidity and neurodevelopmental outcome was analysed. Results: Girls less frequently suffered from early-onset sepsis than did boys (p0.030). After adjustment for multiple corrections (Bonferroni p0.003) no sex differences were seen within any maternal or neonatal parameter. Analysis of morbidity revealed a higher readmission rate in boys (p<0.0001) which was primarily caused by a greater incidence of respiratory problems (p0.003). Boys did not show a greater adverse neurodevelopmental outcome at the age of 12 or 24 months. Conclusion: Parents of boys should be prepared for a potentially higher frequency of readmission after initial discharge, but our data currently give no reason for parents of sons to be disproportionately anxious about their neurodevelopmental outcome. Whether boys also enjoy a rosy prognosis for developmental outcome at school age remains to be elucidated.